Validity And Reliability Of Parents' Knowledge And Attitudes Toward Hearing Impairment In Children Questionnaire Adaptation In Bahasa Indonesia - Annisa Nurul Khakimah; Dewi Pratiwi; Novi Primadewi (Eduvest - Journal of Universal Studies, 2026)
Hearing impairment in children is a health issue that significantly affects communication abilities and social development. The role of parents is crucial in the early detection and intervention process, which is influenced by the level of knowledge and attitude toward the child’s condition. The research aim to evaluate the validity and reliability parents' knowledge and attitudes toward hearing impairment in children questionnaire adaptation in bahasa indonesia. In the context of the Deaf Family Solo Raya (DFSR) community.  This research employed a descriptive quantitative approach with a cross-sectional design. The sample consisted of 30 parents who are members of the DFSR community. The instrument used was a questionnaire adapted from the 2007 Position Statement and studies by Kaspar et al. and Alsudays et al., comprising 25 items on knowledge and 6 items on attitude. Validity was tested using Pearson correlation, and reliability was assessed using Cronbach’s Alpha. The relationship between variables was analyzed using Pearson correlation with the assistance of SPSS version 26. All items on the knowledge and attitude variables were declared valid (p < 0.05) and reliable, with Cronbach’s Alpha values of 0.963 (knowledge) and 0.761 (attitude). A significant positive correlation was found between parental knowledge and attitudes toward childhood hearing loss (r = 0.761; p = 0.000). A high level of knowledge is closely associated with a positive attitude in addressing childhood hearing loss. This study recommends the importance of community-based educational and parental empowerment programs to support optimal early detection and intervention.